PENGARUH E-SERVICE QUALITY DAN E-WOM TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN PADA PENGGUNA MARKETPLACE TOKOPEDIA - Ayu Setia Ningtias; Sugiyanto (CV. Adiba Aisha Amira, 2023)
To retain consumers and make them loyal to the same marketplace is a challenge that companies need to pay attention to. This study aims to study the effect of E- Service Quality and E-WOM on Repurchase Interest through Consumer Satisfaction in Tokopedia marketplace users. The research method used in this study uses path analysis (Path analysis) the type of data used in this study is quantitative. The sample in this study amounted to 170 respondents using a purposive sampling technique. Data collection using questionnaires distributed via Google Form. The results of this study indicate that E-Service Quality and E-WOM have a positive and significant effect on consumer satisfaction in Tokopedia marketplace users. Consumer Satisfaction affects Repurchase Interest in Tokopedia marketplace users. E-Service Quality has no significant effect on Repurchase Interest among Tokopedia marketplace users. E-WOM has a positive and significant effect on Repurchase Interest in Tokopedia marketplace users. E-Service Quality has a positive and significant effect on Repurchase Intention mediated by consumer satisfaction on Tokopedia marketplace users. E-WOM has no effect on Repurchase Intention in mediating Consumer Satisfaction in Tokopedia marketplace users.